Comparative single-cell immune responses in peripheral blood and lymph node of immunized SARS-CoV-2 challenged infant rhesus macaques - Anronikov, Sasha; Meikle, Cameron; Milligan, Emma C.; Chen, Han; Mukherjee, Nilanjan; Bjornson, Zach; Gaudillière, Brice; Jiang, Sizun; Permar, Sallie R.; Van Rompay, Koen K. A.; Nolan, Garry P.; De Paris, Kristina; et al. (Frontiers in Immunology, 2025)
IntroductionA better understanding of post-exposure immune responses in vaccinated individuals, particularly infants, is needed.MethodsUsing a rhesus macaque model, we compared recipients of mRNA- or protein-based SARS-CoV-2 vaccines administered in infancy with unvaccinated controls 7 days post-SARS-CoV-2 virus challenge. Mass cytometry profiling of peripheral blood mononuclear cells and dissociated mediastinal lymph node cells at 7 days post-challenge revealed tissue-specific differences between groups, representing a snapshot of immune activity at this point.ResultsVaccinated animals showed lower frequencies of activated CD8+ T cells in blood and lower levels of monocyte and B cell subsets in lymph nodes, aligning with lower viral loads and milder pathology. Plasmacytoid dendritic cells—commonly depleted in circulation during severe human COVID-19—were preserved in the blood of vaccinated groups. Ex vivo stimulation demonstrated heightened inflammatory cell signaling from unvaccinated rhesus macaques, correlating with worse clinical outcomes.DiscussionThese findings enhance our understanding of a critical nonhuman primate model and underscore the utility of single-cell, tissue-level analyses in evaluating next-generation pediatric SARS-CoV-2 vaccine strategies.